Metaphorical expressions and ethical appeals in Said Nursi’s Damascus Sermon - Abdullah, Nur Sakinah Thomas; Hossein, Vahid Nimehchisalem; Mohd Kasim, Zalinah; Mohamad Ali, Afida; Gulerce, Hakan (Human Resource Management Academic Research Society, 2017)
Contemporary cognitive linguistics views metaphor as pervasive in thoughts and conceptual in nature. There are studies on conceptual metaphors in religious discourse, but little is known about how orators make use of them and ethos (ethical appeals) to influence their audience. This paper reports the results of an explanatory case study of an influential Muslim thinker and theologian, Bediuzzaman Said Nursi’s (1877-1960) ethos and conceptual metaphors in his Damascus Sermon (1911). Specifically, this study identifies and interprets the metaphorical expressions used by Nursi which helps him establish his ethos to strengthen his persuasion. The classical rhetorical theory is employed to examine the ethos while Lakoff and Johnson's (1980) cognitive theory of metaphor is also used. The analysis of the Sermon involves three main stages: i) identification of phrases that indicate ethos, ii) identification of linguistic metaphors using the Metaphor Identification Procedure by Pragglejaz Group (2007) and iii) identification of the underlying conceptual mapping of the expressions. The findings show how Nursi’s use of conceptual metaphors has contributed to the effectiveness of his ethical appeals to persuade his audience. This study sets an antecedent for future studies on conceptual metaphors in religious discourse as a mechanism for rhetorical appeals.